The influence of attitude and social demograpic to the interest for entrepreneurship at school of economics Purna Graha in Pekanbaru - Siti Mariana; Raden Lestari Ganarsih; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was done in kampus Purna Graha on the street Nangka, Pekanbaru. The purpose of this research to eximine attitude and social demographic to the interest for entrepreneurship in School of Economics Student Purna Graha Pekanbaru.Populations of this research is were student Purna Graha School with major on Accountacy and Management. The number of populatios were 1.063. are the sample were 91 person. Writer uses descriptive quantitative regression using SPSS version 20.00.The results shows that simultaneous regression test (F test) attitude and socio demographic has positive and significant effect to dependent variable (interest for entrepreneurship). The effect is 29,6 %, the other 70,4% is affected by other variables, which were not studied in this research. Partial test (t test) show that the independent variables (Attitude) have positive and significant effect to dependent variable. For on the other hand, social demographic variable, were found not significant to interest of entrepreneurship.Keywords: Attitude, Interest For Entrepreneurship, and Social Demographic.